P018 Susceptibility profile of Candida albicans causing bloodstream infections against azole antifungals over 5 years: A prospective observational study. (20th September 2022) - Sharma, Megha; Ahmad, Raees; Ghosh, Anup; Rudramurthy, Shivaprakash; Chakrabarti, Arunaloke
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM:   Objectives: To study the drug susceptibility profile of Candida albicans isolated from bloodstream infection (BSI) against azole anti-fungal agents (fluconazole, itraconazole, voriconazole, and posaconazole) in a tertiary care hospital over 5 years. Methods: All blood culture bottles from patients attending our tertiary care hospital between January 2017 to December 2021 and growing Candida albicans were included in the analysis. All blood culture bottles were continuously monitored automatically inside BACTEC 9240 (BD Becton Dickinson, USA). Beep-positive bottles were further processed by preparation of Gram stain smears, sub-culture onto 5% sheep blood agar and MacConkey agar and spot inoculation onto Sabouraud's Dextrose agar (SDA). Isolates were identified as C. albicans using MALDI-TOF MS (Bruker Daltoniks, Bremen, Germany). Broth microdilution (BMD) was performed to determine minimum inhibitory concentration (MIC) of fluconazole, itraconazole, voriconazole, and posaconazole, in accordance with CLSI document M27-A3 and CLSI M27-S4. Representative isolates were further processed to determine the genetic basis of azole resistance (results will be shared at the conference). Results: A total of 889 C. albicans were isolated from BSI over 5 years. The rates of resistant were 0.9%, 4.3%, and 1.4%; and that of susceptible dose dependent were 0.8%, 28.5%, and 0.4% for fluconazole, itraconazole, and voriconazole respectively (Fig. 1). The MIC90 of the isolates to fluconazole, itraconazole, voriconazole, and posaconazole were 2  μ g/ml, 0.25  μ g/ml, 0.5  μ g/ml and 0.25  μ g/ml, respectively (Fig. 2). Conclusion: Azole antifungals continue to retain favorable MIC90 against C. albicans BSI isolates. Flucanozole continues to be the favored drug of choice due to low side-effects, cost-effectiveness, and least resistant rates.